NOVO COMPLEXO MONONUCLEAR DE ZN(II) COMO MODELO BIOMIMÉTICO DE RELEVÂNCIA BIOINORGÂNICA - MATOS, Daniela Bueno; NASCIMENTO, João Paulo da Cruz; FACCO, Janaína Thomasi; CABEZA, Natalia Aparecida; DOS ANJOS, Ademir (ANAIS DO ENIC, 2018)
-